2000
DOI: 10.1103/physrevd.61.045009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical chiral symmetry breaking on the light front: DLCQ approach

Abstract: Dynamical chiral symmetry breaking in the discretized light-cone quantization method is investigated in detail using a chiral Yukawa model closely related to the Nambu-Jona-Lasinio model. By classically solving three constraints characteristic of the light-front formalism, we show that the chiral transformation defined on the light front is equivalent to the usual one when the bare mass is absent. A quantum analysis demonstrates that a nonperturbative mean-field solution to the ''zero-mode constraint'' for a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(97 citation statements)
references
References 39 publications
6
90
1
Order By: Relevance
“…The difficulty of describing massless particles is intimately connected with the fact that on the LF, the (massless) Nambu-Goldstone boson becomes physically meaningful only when we first include explicit breaking term and then take the vanishing limit of it [12]. The same situation was observed in the chiral Yukawa model [4].…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…The difficulty of describing massless particles is intimately connected with the fact that on the LF, the (massless) Nambu-Goldstone boson becomes physically meaningful only when we first include explicit breaking term and then take the vanishing limit of it [12]. The same situation was observed in the chiral Yukawa model [4].…”
Section: Introductionmentioning
confidence: 85%
“…The procedure of Ref. [4] is as follows: First, we formally solved the fermionic constraint (2.18) and substitute the solution into the zero-mode constraints (2.17). Second, we solved the zero-mode constraints by 1/N expansion with a fixed operator ordering and found that the leading order of the scalar zero-mode constraint can be identified with the gap equation.…”
Section: Implication Of the Fermionic Constraintmentioning
confidence: 99%
See 3 more Smart Citations